Methane in sulphides from gold-bearing deposits, Britain and Ireland. Issue 3 (3rd July 2019) - Parnell, John; Spinks, Sam; Blamey, Nigel
ABSTRACT: The direct measurement of gases trapped in sulphide minerals shows that samples from gold-bearing deposits in Britain and Ireland are anomalously rich in methane. Chalcopyrite samples in deposits of Palaeozoic age sited in Neoproterozoic basement (Caledonides greenschist), Munster Basin (Variscides greenschist) and the Carboniferous cover (diagenetic) were compared using mass spectrometry of cold-crushed gases. All host sequences contain sources of organic matter. The content of non-aqueous gas is greater in both sets of greenschist-hosted deposits than in the diagenetic-hosted deposits. However, chalcopyrite accompanying gold in the Neoproterozoic is methane-rich, but in the low-gold Munster Basin it is methane-poor. These gas data from opaque minerals complement fluid inclusion data from gangue minerals, and add support to models for the involvement of organic species in orogenic gold mineralisation.